2022
DOI: 10.1002/wsb.1372
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation structure and food availability following disturbance in recently restored early successional plant communities

Abstract: Fields dominated by nonnative grasses, such as tall fescue (Schedonorus arundinaceus), are being restored to native plant communities across the eastern U.S. Upon restoration, disturbance is necessary to maintain native communities in an early seral stage, and plant response to different management practices is of interest to managers to guide habitat enhancement for various wildlife species. We evaluated effects of burning and mowing following restoration of native plant communities via 2 methods (planting na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Many managers opt to plant native grasses and forbs following initial control of nonnative species, while failing to recognize they may have to kill the planted forbs to control incoming sericea. Our data indicated that managing the seedbank response often is a more effective and efficient approach to restoring early successional plant communities for bobwhite than planting native grasses and forbs (GeFellers et al 2020, Harper et al 2021, Powell et al 2022).…”
Section: Discussionmentioning
confidence: 83%
“…Many managers opt to plant native grasses and forbs following initial control of nonnative species, while failing to recognize they may have to kill the planted forbs to control incoming sericea. Our data indicated that managing the seedbank response often is a more effective and efficient approach to restoring early successional plant communities for bobwhite than planting native grasses and forbs (GeFellers et al 2020, Harper et al 2021, Powell et al 2022).…”
Section: Discussionmentioning
confidence: 83%
“…To combat this, biologists increasingly call for conservation practices that emulate ecological disturbances to be implemented (e.g., prescribed fire, timber harvesting, and shrub-shearing; Askins 2001, Swanson et al 2011). The benefits of these conservation practices to vertebrate animals has been documented widely (Artman et al 2001, Zwolak 2009, Fontaine and Kennedy 2012, Hocking et al 2013, McNeil et al 2020, Hunter and Rostal 2021, Litvaitis et al 2021, Powell et al 2022) but remains relatively less studied for invertebrates (like pollinators; Campbell et al 2007, Romey et al 2007, Mathis et al 2021).…”
Section: Introductionmentioning
confidence: 99%